Activation of oxygen with sulfite for enhanced Removal of Mn(II): The involvement of SO4-. (15th June 2019) - Rao, Dandan; Sun, Yuankui; Shao, Binbin; Qiao, Junlian; Guan, Xiaohong
Abstract: Taking advantage of the active oxidants generated in the process of Mn(II)-catalyzed sulfite oxidation by oxygen, this study sought to enhance Mn(II) removal from water by activating oxygen with sulfite. The results revealed that Mn(II) can be effectively oxidized by oxygen to MnO2 with the addition of sulfite under environmentally relevant conditions, and the performance of this process is dependent on the dosage of sulfite and the initial pH. Mn K -edge XANES analysis indicates that Mn(II) removal is primarily due to the transformation of Mn(II) to MnO2 and, secondarily, to the adsorption of Mn(II) on generated MnO2 . Co-existing NaCl and CaCl2 negatively affect Mn(II) removal, while the presence of Fe(II) considerably enhances Mn(II) removal by improving both Mn(II) oxidation and Mn(II) adsorption on the generated solids. Consequently, Mn(II) removal is as high as 98% in the presence of 1.0 mg/L of Fe(II) and both the residual Mn (<0.1 mg/L Mn) and Fe (<0.3 mg/L Fe) can meet China's drinking water standard. The experiments with real water samples also demonstrate the effectiveness of the sulfite-promoted Mn(II) removal process, especially in the presence of Fe(II). The enhancing effect of sulfite on Mn(II) oxidation by oxygen is mainly associated with the generation of HSO5 −, and the critical step for generating HSO5 − is the rapid oxidation of SO3 - by oxygen. EPR and radical scavenging studies demonstrate that SO4 - radical is the key reactive oxygen species responsible for Mn(II) oxidation by HSO5 − . Graphical abstract: Image 1 Highlights: Mn(II) can be effectively oxidized by oxygen in the presence of sulfite. Sulfite-promoted Mn(II) removal is dependent on pH and sulfite concentration. HSO5 − is generated in this process and contribute to Mn(II) oxidation. SO4 . - is the key radical responsible for Mn(II) oxidation by HSO5 − . Fe(II) can enhance sulfite-induced Mn(II) removal.